Penentuan Parameter Bioavailabilitas Isolat Andrografolida Dalam Bentuk Dispersi Padat Dengan Matriks PEG 8000 Pada Kelinci Dengan Penetapan Kadar Secara HPLC - Ummi Fasilah, - (2004)
Andrographolide is a poorly soluble substance, however the disolution rate of which can be enhanched by solid dispersion with Polyethylen Glycol – 8000 (PEG 8000) adsorbed to spray dried lactose. The solid dispersion system was prepared in the ratio andrographolide – PEG 8000 – spray dried lactose = 1 : 5 : 5 in order to improve disolution rate. Andrographolide solid dispersion with a single-dose given peroral to the white male rabbits (n = 3) respectively 2.6 mg/kg of body weight. The serum concentration of andrographolide were estimated by High Performance Liquid Chromatography (HPLC) before, and 15, 30, 45, 60, 90, 120, 180, 360, 540, 720 minutes after oral administration. Andrographolide was extracted from serum using methanol. A Varian HPLC (model 9012 Q) with UV-vis spectrophotometric detector (model 9050) were used for andrographolide estimation. A Licrosorb reverse phase C18 column (10 μ, 250 x 4 mm) was used. The mobile phase used was methanol : water in the ratio of 60 : 40 v/v at flow rate of 1.0 ml/min. The elutes were monitored at 228 nm. The time to reach peak serum concentration tmax were 15 – 30 minute. Peak serum concentration Cmaks were 7,2691 – 8,6236 μg/ml. The area under the serum concentration-time curve (AUC) 2142,2505 - 2357,5995 μg min/ml. 7200